Epidemiological Distribution of Major Ectoparasites Species of Small Ruminant in the Case of Chemical Control Campaign in Welkait District, Tigray Region, Ethiopia - Berhe Leul; Afera Berihun; Kebede Etsay (Journal of Tropical Medicine)
A cross-sectional study was carried out from November 2016 to May 2017 to identify the major ectoparasites species and potential risk factors in Welkait district western part of Tigray region. A total of 102 sheep and 324 goats were physically examined and samples were taken for laboratory analysis. Rhipicephalus evertsi evertsi with a prevalence of 58 (56.86%), Amblyomma gemma 12 (11.76%), Amblyomma variegatum 27 (26.47%), Boophilus decoloratus 7 (6.86%), and Hyalomma anatolicum excavatum 1 (0.98%) in sheep and R. evertsi evertsi 108 (33.02%), A. gemma 8 (2.47%), A. variegatum 158 (48.77%), and R. B. decoloratus 19 (5.86%) in goats were the most important tick species identified. Statistically significant difference (p<0.05) was obtained in the prevalence of A. gemma (x2 = 14.981; p=0.001) and A. variegatum (x2 = 15.696; p=0.001) between sheep and goats and R. B. decloratus (x2 = 8.137; p=0.017), A. variegatum (x2 = 90.159; p=0.00p=0.00), and A. gamma (x2 = 18.642; p=0.00) in goats and A. variegatum (x2 = 71.081; p=0.00) and R. B. decloratus (x2 = 28.980; p=0.001) in sheep by agroecology. R. evertsi evertsi (x2 = 13.400; p=0.001) and A. variegatum (x2 = 13.511; p=0.001) in goats and R. B. decoloratus (x2 = 71.892; p=0.001) and A. gemma (x2 = 6.414; p = 0.040) in sheep were found to have statistically significant association (p<0.05) in the prevalence among different body condition categories in the present study. R. evertsi evertsi (x2 = 6.557; p=0.010) and R. B. decoloratus (x2 = 4.856; p=0.028) in goats and R. evertsi evertsi (x2 = 5.776; p=0.016) in sheep by sex group and R. evertsi evertsi (x2 = 40.556; p=0.001) and A. variegatum (x2 = 7.214; p=0.007) in goats by age group were also statistically associated (p<0.05). Infestation rate of R. evertsi evertsi (x2 = 7.136; p=0.008), R. B. decoloratus (x2 = 9.621; p=0.002), and A. variegatum (x2 = 10.372; p=0.001) in goats between flock type had statistically significant association (p<0.05) in this study. The current result revealed that Linognathus stenopsis was the second highest prevalent ectoparasite with an overall prevalence of 0.00% in sheep and 25.93% in goats. There was a statistically significant difference (p<0.05) in the prevalence of L. stenopsis (x2 = 32.940; p=0.001) between the two species and in body condition category (x2 = 10.700; p=0.005) in goats in the present study. Moreover, Ctenocephalides canis and Ctenocephalides felis were the flea species found in the present report. Significant variation (p<0.05) in C. canis prevalence among different agroecology (x2 = 10.264; p=0.006) in goats and between adult and young age (x2 = 5.052; p=0.025) in sheep and (x2 = 21.267; p=0.001) in goats was obtained in the present study. Sarcoptes scapie var. caprea with a prevalence of 0 (0.00%) in sheep and 4 (1.23%) in goats had no significant association (p>0.05) in all the risk factors considered. The present result indicated that ectoparasites especially tick species were more prevalent in small ruminants and may affect the wellbeing and productivity of goats and sheep in the study district. Therefore, well-coordinated and urgent control intervention should be conducted.